Notary/PPAT Liability for Autenticity of Deed which in Judges' Decision is Declared to Have Fake Signature - Dadan Taufik Fathurohman; Sri Kusriyah; Amin Purnawan (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
The purpose of this research is to find out and analyze the juridical implications of making a deed in which there is a forged signature. This study used a normative juridical research method. Based on the discussion, it can be concluded that the juridical implications for the making of a deed in which there is a fake signature is that it can be canceled or null and void because it does not meet the subjective requirements in the form of agreeing the parties and the objective conditions in the form of a lawful cause. In addition, the making of a deed in which there is a forgery of a signature with procedural efforts that are not in accordance with the making of the deed results in the deed being formally flawed.